2017
DOI: 10.3892/etm.2017.5314
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin suppresses AGEs induced apoptosis in tubular epithelial cells via protective autophagy

Abstract: Renal tubular cell apoptosis and tubular dysfunction is an important process underlying diabetic nephropathy (DN). Understanding the mechanisms underlying renal tubular epithelial cell survival is important for the prevention of kidney damage associated with glucotoxicity. Curcumin has been demonstrated to possess potent anti-apoptotic properties. However, the roles of curcumin in renal epithelial cells are yet to be defined. The present study investigated advanced glycation or glycoxidation end-product (AGE)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
(22 reference statements)
0
17
0
Order By: Relevance
“…Previous researches have shown that high glucose promoted autophagy in endothelial cells by inhibiting PI3K/AKT signaling [ 7 ]. While in RPE cells, autophagy can prevent the oxidative damage caused by diabetes [ 22 ]. We have revealed that autophagy has a positive effect on RPEs under intermittent high glucose condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have shown that high glucose promoted autophagy in endothelial cells by inhibiting PI3K/AKT signaling [ 7 ]. While in RPE cells, autophagy can prevent the oxidative damage caused by diabetes [ 22 ]. We have revealed that autophagy has a positive effect on RPEs under intermittent high glucose condition.…”
Section: Discussionmentioning
confidence: 99%
“…Astilbin [140], astragaloside IV [15], curcumin [41], Psoralea corylifolia [115], quercetin [49], secoisolariciresinol diglucoside [88], silybin [43], berberine [45], berberine [44], berberine [136], tripterygium glycosides [138], celastrol [170], curcumin [132], resveratrol [133], astragaloside IV [103], Cyclocarya paliurus-triterpenic acids-enriched fraction [142], ferulic acid [145]…”
Section: Apoptosismentioning
confidence: 99%
“…Astilbin [140], astragaloside IV [15], emodin [94], Hypericum perforatum [31], berberine [45], berberine [44], curcumin [132], resveratrol [133], resveratrol [168], astragaloside IV [103], Cyclocarya paliurus-triterpenic acids-enriched fraction [142] Tangshen Formula [123] Collagen 4…”
Section: Hif-1α/pi3k/aktmentioning
confidence: 99%
See 2 more Smart Citations